Diff erential genotypic response of two varieties of Hordeum vulgare L. in response to hydrazine hydrate alone and in combination with dimethyl sulfoxide - Sadia Fatima, Samiullah Khan, Shahnawaz Khursheed, (Journal of Phytology, 2015)
Induced mutation has been an important tool for a man in bringing desirable changes in plants since times immemorial. Cereals form an integral part of human diet along with pulses, especially in India. Cereals contain a high percentage of carbohydrates along with the considerable amount of proteins. The present experiment was carried out to induce the variability in Hordeum vulgare L. variety RD-2035 and BH-393. The mutagen used in this experiment was hydrazine hydrate (Hz). The mutagen was used singly and in combination with dimethyl sulfoxide (DMSO). Usually, the DMSO is considered as a carrier for a mutagen to enhance the mutagenic activity of that particular mutagen used in combination. The two varieties of seeds were treated with individual concentrations of Hz along with combination treatments with DMSO. The seeds were sown to raise the M1 generation. Cytology of both control and treated plants was observed in the M1 generation. The control plants showed normal meiosis, whereas the treated plants showed different chromosomal abnormalities. The different chromosomal abnormalities were laggard, bridge, micronucleus, and univalents. The meiotic abnormalities were low at lower concentrations of both individual and combination treatments while as the percentage abnormalities increased with increasing concentrations of both individual and combination treatments. M1 seeds were sown to raise the M2 generation. Quantitative characters of both control and treated plants were observed. The lower concentrations of both individual and combination treatments induced desirable changes in quantitative characters while as the higher ones induced negative effects.